Identification of novel hub genes and pathways predictive of fibrosis progression in cancer-related lymphedema through integrated multi-omics - Chen, Junzhe; Chen, Yuezhong; Wang, Liangliang; Deng, Yaping; Zhou, Yan; Wang, Yun; Xiao, Shune; Deng, Chengliang (Frontiers in Immunology, 2025)
BackgroundCancer-related lymphedema (CRL) is a common chronic complication following cancer treatment, characterized by impaired lymphatic drainage, interstitial fluid retention, and progressive fibrosis. Although the mechanisms of hypertrophic scar (HTS) fibrosis have been extensively investigated, the molecular drivers of fibrosis in CRL remain unclear. Identification of reliable biomarkers and novel therapeutic targets is essential for enabling early intervention.MethodsTranscriptomic datasets of CRL and HTS from the Gene Expression Omnibus (GEO) were integrated to identify fibrosis-associated differentially expressed genes (DEGs) and construct co-expression modules. Weighted gene co-expression network analysis (WGCNA) and protein–protein interaction (PPI) network analysis were employed to nominate hub genes. Single-cell RNA sequencing (scRNA-seq) data were used to localize candidate gene expression within immune and mesenchymal cell populations. The most promising biomarker was validated in clinical CRL tissues by Masson’s trichrome staining and Western blotting, and Pearson correlation analyses were performed to assess its association with collagen deposition and disease duration.ResultsA total of 154 fibrosis-related genes were found to be shared by CRL and HTS. Among them, Asporin (ASPN) emerged as the most promising hub gene, with markedly elevated expression in late-stage CRL tissues. scRNA-seq analysis revealed that adipose-derived stem cells (ADSCs) were the predominant ASPN-expressing population. In CRL lesions, ASPN expression levels showed significant positive correlations with disease duration, TGF-β expression, and collagen accumulation.ConclusionsASPN is identified as a key molecular biomarker of fibrosis in CRL. Its predominant expression in ADSCs and strong association with progressive tissue remodeling suggest that ASPN holds potential as both a diagnostic indicator and a therapeutic target for CRL-related fibrosis.